Treatment of lipolysis of submental fat with ozone therapy and its effects on chronic and aesthetic obstructive apnea syndrome (Ozone Therapy Global Journal, 2020)
The fat accumulation in the submental region represents a significant aesthetic disadvantage, causing the double chin and also implies a serious health problem, as it is associated with sleep apnea, oxidative stress and even death from cerebral hypoxia and respiratory failure in a large part of the population worldwide. This study aimed to evaluate ozone therapy as a safe tool to treat excess of fat in the submental region, as the other procedures commonly used have questionable side effects, such as a liver overload function and changes in homeostasis. The study is a review of the literature with ozone therapy, its administration forms, concentrations, periodicity, contraindications, in the prescribed situations and comorbidities to evaluate an effective and safe therapeutic proposal in the volumetric reduction of submental fat. The data bases reviewed were MedLine databases of PubMed and Zotero ISCO3 of the articles published between 1990 to 2020, using the keywords: ozone therapy, obstructive sleep apnea, submental fat, lipolysis. The study suggests that ozone therapy is effective and has a low incidence of side effects, although requires more clinical studies with large samples to establish protocols in its application, with patient follow-up for a longer time to verify the efficacy of long-term treatment.